The Temperature Evolution of the Out-of-Plane Correlation Lengths of Charge-Stripe Ordered La(1.725)Sr(0.275)NiO(4) - Freeman, P; Christensen, N; Prabhakaran, D; Boothroyd, A (2009)
The temperature dependence of the magnetic order of stripe-ordered La(1.725)Sr(0.275)NiO(4) is investigated by neutron diffraction. Upon cooling, the widths if the magnetic Bragg peaks are observed to broaden. The degree of broadening is found to be very different for l = odd-integer and l = even-integer magnetic peaks. We argue that the observed behaviour is a result of competition between magnetic and charge order.